Familiarizing Research Methodology and Biostatistics (Advancements in Homeopathic Research, 2022)
An Institution’s Quality is known by the Research works going on there and the quality of such Research works are determined by the availability of the qualified and dedicated faculty. But in Academic Institutions the scenario is different. That is even with the availability of the well qualified staffs and highly equipped infrastructure the research ability is dependent on the students. Staffs can coordinate the Research projects; but the Research Processes are to be laid by the students. In the Medical Academic Institutions this responsibility is greatly carried by the CRRI and Postgraduate students. For carrying out a Research the students are to be well aware of the “Research Methodologies” and to justify their results scientifically they should know the “Basics of Bio-statistics”. But most of the times the students feel these subjects as Nightmare and study in the purview of getting pass in the examinations. Even many academic staffs are not much interested in the Research methodologies & Biostatistics as they feel those subjects are strange. So that many researches are done in the old dogmatic ways giving results more of quantitatively with less quality. Such results are not sufficient to be accepted by the Scientific Fraternity as they were not strictly carried out by the Principles of Research methodology and not Bio-statistically valid. Hence in this writing I wish to sum up the essence of the Research methodology and Bio-statistics in a simple understandable manner so as anyone who wishes to do a research can get benefited.
Keywords: subjects; Bio-statistically; Fraternity; Research